Pelatihan Media Powerpoint untuk Mengembangkan Pembelajaran Kreatif di Taman Kanak Kanak - Wulandari, Hayani; Amalia, Hanny Anisa; Shohabi, Abdillah Fata; Hendriani, Indri; Anmbia, Nayna Nurul; Saputri, Ovie Nurkholizah; Riani, Sari (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2022)
Technological developments make education in Indonesia have to accept todays’s technological learning change. However, in technological progress, there are still many educators who are still unfamiliar with technology that can be used for learning media in schools, such as the lack of adewuate technology development training in classroom learning to develop teacher abilities that can be used in learning activities. The pupose of the activity is to develop the ability of teacher to create creative learning media in school using power point. The implementation method is the planning stage, the preparation stage, and the evaluation stage. Based on observation during the training, the teacher showed an entusiastic attitude because this PowerPoint media was a new thing in learning at Kinderganten Plus Tunas Rimba. Teachers got new knowledge about using PowerPoint as an effective technology –based learning media that is interesting and fun for children. This activity is a form of training for teacher in carrying out learning activities and teaching supporting media for children’s online learning.